Perbedaan Tekanan Darah Pada Pekerja Yang Terpapar Panas Di Industri Sale Pisang Suka Senang Kabupaten Ciamis - Suwondo, Ari; Lestantyo, Daru; Yulisnawati, Yulisnawati (Jurnal Promosi Kesehatan Indonesia, 2008)
Background: Heat stress is one of the physical factors in work environment which become additional risk for labors. The influence of heat stress in peripheral venous dilatation will disturb the balance of blood circulation. Labors that always under heat exposed during workingrequires enough of drinking water and it is better consumed in a little but more frequent. This research purpose is to know difference of blood pressure at worker which heat exposed with difference pattern of drinking water consumption.Method: This research type is Quasi-Experimental, by using One Group Pre and Post Test Design. Amount of samples are 21. Research has done in frying department of traditional banana cake in District of Ciamis . The data analyzed by using paired t-Test.Result: The result of this research indicates that, there is a significant different of blood pressure between workers using drinking pattern I and II (p = 0.0001). As a suggestion for this industry are enlarge the ventilation volume at the roof of building, installing fan with adjustable design, providing comfortable rest room, enough drinking water at the nearest places that can be easily reached by labors.Keywords: Heat Stress, blood pressure, drinking water.